2007
DOI: 10.1080/10412905.2007.9699304
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Leaf and Fruit Oils ofHeracleum candolleanum

Abstract: Essential oils from leaves and fruits of Heracleum candolleanum were obtained by hydrodistillation and analyzed by GC and GC/MS. The major components in the leaf oil were sabinene (13.2%), limonene (9.2%), β−caryophyllene (8.6%) and caryophyllene oxide (8.4%), whereas the major constituents in the fruit oil were limonene (70.0%) and octyl acetate (7.2%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…p-Cymene was the only phenolic compound identified, while oxygenated aliphatic hydrocarbons and sequiterpene hydrocarbons were present in trace amounts. Components such as limonene, octyl acetate, bornyl acetate were also reported from the oils of H. candolleanum and H. siamicum [5,6]. Further octyl acetate was a prominent component in H. persicum, H. rechingeri, H. transcaucasicum, H. crenatifolium, H. platytanium and H. sphondylium L. subsp.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…p-Cymene was the only phenolic compound identified, while oxygenated aliphatic hydrocarbons and sequiterpene hydrocarbons were present in trace amounts. Components such as limonene, octyl acetate, bornyl acetate were also reported from the oils of H. candolleanum and H. siamicum [5,6]. Further octyl acetate was a prominent component in H. persicum, H. rechingeri, H. transcaucasicum, H. crenatifolium, H. platytanium and H. sphondylium L. subsp.…”
mentioning
confidence: 95%
“…The seed oil of H. candicans, H. lehmannianum, H. ponticum and H. aconitifolium have been evaluated for various ailments [3,4]. The extraction of the seed oils and their chemical compositions were reported for H. condolleanum and H. siamicum [5,6]. Due to the absence of any such studies in H. rigens, the present study was undertaken to evaluate the chemical composition of the essential oil and its antimicrobial activity on selected pathogenic bacterial strains.…”
mentioning
confidence: 99%
“…[16,17], H. platytaenium Boiss. [16], and H. candolleanum [18]. These oils contain monoterpene hydrocarbons (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They are reported to be effective in indigestion, sunburn, skin diseases, and external tumours (Heywood, 1971). Many studies reported on the biological activities and essential oil composition of the genus Heracleum (Ergene et al, 2006;John et al, 2007). As part of our on-going studies on the genus Heracleum from Western Ghats of India, we now report on the composition of the volatile oils of the fruits of H. aquilegifolium for the fi rst time, together with their antioxidant properties.…”
Section: Introductionmentioning
confidence: 95%